PERFORMANCE ANALYSIS OF MANAGEMENT UNIT ACTIVITIES OF THE EX-PNPM Savings and Loans COMMUNITY EMPOWERMENT TRUST FUND FOR WOMEN'S GROUPS 2017 – 2020 IN SEJANGKUNG DISTRICT - Mulyanto, Yayan (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
-